Zhachong Shisanwei Pill resists ischemic stroke by lysosome pathway based on proteomics and bioinformatics. (30th January 2023) - Song, Qi; Bi, Lei; Jiao, Jiakang; Shang, Jinfeng; Li, Qiannan; Shabuerjiang, Lizha; Bai, Meirong; Liu, Xin
Abstract: Ethnopharmacological relevance: Zhachong Shisanwei Pill (ZSP) is a commonly used Mongolian medicine in treating cerebrovascular diseases and plays a role in the clinical treatment of ischemic stroke (IS). Aim of the study: Based on determining the protective effect of ZSP on cerebral ischemia, they adopted the proteomics method to explore the mechanism of ZSP against IS. Materials and methods: Rats with middle cerebral artery occlusion (MCAO) model were prepared by wire embolization method, and divided into sham group, model group, ZSP high-dose group, medium-dose group, low-dose group and positive drug group. We collected the brain tissue of rats for 12 h after modeling. Neurological deficit score and cerebral infarction volume ratio evaluated pharmacodynamics, and we selected the optimal dose for subsequent experiments. Proteomics was used to screen out possible ZSP anti-IS mediated pathways and differentially expression proteins. Network pharmacology was used to verify the correlation between diseases and drugs. Hematoxylin-eosin (HE) staining and transmission electron microscope (TEM) were used to explore further the pharmacodynamic effect of ZSP against IS and its possible mechanism. Results: The cerebral infarction rate and neurological function score in rats showed that the medium-dose ZSP group had the best efficacy. Proteomics results showed that the anti-IS action of ZSP was mainly through lysosome pathway. LAMP2, AP3M1, and SCARB2 were the differentially changed proteins in this pathway. Network pharmacology verified this. HE staining and TEM results showed that ZSP could improve the pathological state of neurons in MCAO rats and reduce the number of lysosomes in MCAO rats. Western blot (WB) results showed that compared with the model group, the protein expression levels of LAMP2 and AP3M1 in the ZSP group were significantly down-regulated, and the protein expression levels of SCARB2 were significantly up-regulated. Conclusion: This study confirms that ZSP regulates the lysosomal pathway, which may protect IS by down-regulating LAMP2 and AP3M1 and up-regulating SCARB2. Graphical abstract: Image 1 Highlights: ZSP has pharmacological effects on cerebral ischemia. This study combined proteomics and bioinformatics. ZSP may regulate the lysosomal pathway. ZSP ameliorates cerebral ischemia by affecting multiple proteins.